Exploration of Knowledge, Attitude, and Practice Among Residents of Saudi Arabia Toward Hepatitis Viruses. (25th November 2021) - Alotaibi, Bashair S.; Althobaiti, Maryam A.; Hazazi, Amal Y.; Hazazi, Sarah Y.; Nassir, Rawan A.; Alhaddad, Mahmoud S.; Abdelwahab, Sayed F.
Background and aim: Data available in the Kingdom of Saudi Arabia (KSA) about public knowledge, attitude, and practice (KAP) toward viral hepatitis infection are scarce. Such information is essential for designing effective intervention strategies for the prevention and control of viral hepatitis. This study aimed to assess the knowledge, attitude, and practice among residents of KSA toward hepatitis viruses.Methods: A cross-sectional descriptive study was conducted among 549 participants in Saudi Arabia. An electronic questionnaire (in Arabic) was used to measure the KAP of the participants. Data were analyzed using SPSS version 23 at significance level of .05.Results: Most of the 549 participants were Saudi citizens (96%; n = 527) and 26.6% (n = 146) of them were males and mostly from the western Saudi Arabia (72.9%; n = 400). Most participants did not hear about hepatitis viruses and showed low level of knowledge on viral hepatitis (42%). On the other hand, a positive attitude was apparent from participants' responses, and their practices were toward protecting their bodies from the infection.Conclusion: The level of knowledge about viral hepatitis was low (42%) among KSA residents, and the practice and attitude of the participants were toward avoiding the infection. Awareness campaigns are required to increase the public knowledge about viral hepatitis.